Deciphering Carlo Ginzburg : form and time - Carneiro, Deivy Ferreira; Rezende Berbert Dias, Daniel (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book offers an original reading of Carlo Ginzburg's work, tracing his trajectory in the context of Italian microhistory, his debates on the objectivity of historical knowledge, and the connection of his work to the expanded perspectives constructed in recent decades by global history. Thought-provoking and thoroughly researched, Deciphering Carlo Ginzburg is an innovative study in Ginzburg's methods and theories"--
Mimetics : between philology and history -- A slave of the thing itself : in defense of the historian's métier -- In search of form : Nachleben, Pathosformeln and Logosformeln -- Catabasis : journey to the world of the dead -- Micro-history and global history -- Perspectivism : Carlo Ginzburg's history of the world.
"Originally published in Portuguese as A forma e o tempo - decifrando Carlo Ginzburg by Alameda, 2022"
Keywords: Ginzburg, Carlo; Microhistory -- Italy; History -- Philosophy; Historians -- Italy -- Biography; HISTORY / Historiography; HISTORY / Europe / General